ANALISIS CERPEN SEPOTONG SURAT DALAM DIAM KARYA ASMA NADIA MENGGUNAKAN PENDEKATAN OBJEKTIF DAN MIMETIK - Syifani Aryanti; Dzira Auliya Marsela (Universitas Maritim AMNI Semarang, 2022)
Literary work is the author's reflection on the reality of life.This study aims to determine the intrinsic and extrinsic elements contained in the short story